PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI SMK ISLAM NUSANTARA COMAL KABUPATEN PEMALANG - Anggraeni, Bety; Harnanik, Harnanik (Dinamika Pendidikan, 2015)
The interest of entrepreneurship is influenced by several factors such as entrepreneurial knowledge and family environment. The result of preliminary observation in SMK Islam Nusantara Comal showed that the entrepreneurship interest of the eleventh grader students in the academic year of 2014/2015 was still considered poor. On the other hand, their entrepreneurial knowledge was pretty high as well as their family environment which was considered good. The objectives of this study were 1) to find out whether or not there is an influence of entrepreneurial knowledge on entrepreneurship interest of the eleventh grader students of SMK Islam Nusantara Comal in the academic year of 2014/2015, 2) to find out the influence of family environment on entrepreneurship interest of the eleventh grader students of SMK Islam Nusantara Comal in the academic year of 2014/2015, 3) to find out the influence of both entrepreneurial knowledge and family environment on entrepreneurship interest of the eleventh grader students of SMK Islam Nusantara Comal in the academic year of 2014/2015. The population of this study was the eleventh grader students of SMK Islam Nusantara Comal in the academic year of 2014/2015 as many as 316 students. The number of sample was 76 students decided by using Slovin calculation formula and chosen using proportional random sampling technique. The methods of collecting the data were test, questionnaire, and documentation. While the methods of analyzing the data were using percentage descriptive technique and multiple linear regression analysis. The result of this study based on the regression analysis it was found that Y = -6,787 + 0,493 X1 + 0,170 X2. The result of hypothesis testing in partial showed that the variable of entrepreneurial knowledge positively influenced the entrepreneurship interest by 32,60% and family environment positively influenced by 18,40%. While simultaneously, the influence of entrepreneurial knowledge and family environment on entrepreneurship interest was 52,70% and the rest 47,30% was explained by other factors beyond the model of this study.